STRATEGI PENGEMBANGAN OBYEK WISATA RAWA KALIBAYEM DESA NGESTIHARJO KASIHAN BANTUL - Susiyanto Susiyanto; Nur Rohman (Pringgitan, 2021)
Strategy development of tourism objects is needed to increase the development of the country. This can be done by making good use of existing potentials and increasing human resource development. One of the attractions that can be utilized and developed is the kalibayem swamp tourism object. The method used in this activity is the method of observation to the object of research.the variables that will be observed in this study are physical conditions, social conditions, economic activities, social culture, policies and regulations. Sources of data used in this study are primary data and secondary data. Regarding the results and discussion, namely: 1) Kalibayem swamp tourism object has many attractions that can be developed and attract the interest of the wider community, namely natural tourism objects supported by very strong cultural tourism. In addition to beautiful scenery, many attractions, facilities and historical value can be obtained by visiting the kalibayem swamp tourist attraction. 2) One of the tourism object development strategies is aimed at the welfare of the community by developing human resources. The strategy for developing the kalibayem swamp tourism object is to use swot analysis and directs to utilize and explore potential, optimize marketing or promotion, improve facilities and infrastructure and maintain environmental sustainability of tourist objects and maintain tourist objects based on historical tourism or cultural tourism.Keywords : Strategy, Development, Tourism, Kalibayem Swamp